Study of Preservation Using Lactic Acid Bacteria from Fermentation of Cabbage (Brassica oleracea var. Capitata) to Shelf Life of Fresh Tilapia (Oreochromis niloticus) - Nesya Joza Amanda; Lukman Hidayat; Wuri Marsigit (AGRITROPICA : Journal of Agricultural Sciences, 2021)
This study aims to determine the best concentration of Lactic Acid Bacteria (LAB) solution from fermented cabbage to tilapia fish during storage. This study used a completely randomized design with the percentage of addition of LAB solution as a treatment (0%, 2%, 4%, 6%). The results of this study indicate that the LAB solution concentration has a significant effect on the physical, chemical, and microbiological quality of fresh fish where the higher the concentration, the higher the resulting value. The LAB solution concentration as the best preservative was found in the LAB solution with a concentration of 6%. The results of the physical properties on the observation of the eyes, gills, meat, and texture met the SNI requirements, namely 7 to the 12th observation hour at a concentration of 6%, but on mucus and odor at the 12th observation hour at a concentration of 2%, 4%, and 6 % still fulfills the SNI requirements, namely 7. The chemical properties at pH until the 24th hour of storage were 6.33 and protein content 21.88%. The microbiological properties of tilapia by giving LAB 6% solution at the 12th-hour observation still met the maximum limit of microorganism growth with a value of the number of colonies/plates 4.2 x 105 cfg / g.